Efektifitas Uji Adaptasi Tanaman Teratai, Eceng Gondok, dan Kangkung dalam Menurunkan Kadar COD, BOD, dan DO dalam Limbah Domestik - Elizabet Matolisi; Alimin Alimin; Marlini Marlini (Biocaster : Jurnal Kajian Biologi, 2026)
Microbiological pollution of river water is one of the major risks to public health. Escherichia coli is used as an indicator of fecal contamination in waters. The Aur River is a tidal river in Palembang City that receives domestic waste runoff from the activities of the surrounding community. This study aims to analyze the total concentration of coliform and identify the dominant coliform type in the Aur River. The research was carried out along 2.5 km with three observation stations (upstream, middle, and downstream). Water sampling was carried out at five points at each station, and coliform analysis referred to SNI 3554. The results showed that the total coliform concentration at the upstream station was 5.24 × 10⁶ ± 1.1 × 10⁵ CFU/100 mL, the middle station was 1.1 × 10⁴ ± 5.5 × 10² CFU/100 mL, and the downstream station was 9.2 × 10⁶ ± 1.1 × 10⁵ CFU/100 mL, all of which exceeded the quality standard of 5 × 10³ CFU/100 mL. The dominant coliform types identified include Klebsiella pneumoniae, Proteus mirabilis, Escherichia coli, and Enterobacter sp. These results show that the Aur River has experienced significant microbiological pollution, so efforts to control and manage water quality in a sustainable manner are needed.